Comparative studies of effect of compound feeds on fish-breeding and biochemical properties of juvenile chum salmon - A. N. Bashtovoy; K. G. Pavel; T. N. Slutskaya; G. N. Timchishina; E. V. Yakush (Известия ТИНРО, 2023)
Effectiveness of starter fodders is examined for the low-temperature rearing pools in the salmon fish hatchery Savushkina (Severo-Kurilsk). In May 2022, the experimental compound feed developed in TINRO was compared with the control fodder Aller Aqua (made in Denmark) when feeding of chum salmon fry. Both fodders complied with the veterinary and sanitary requirements of the Euro-Asian Economic Union in terms of quality and safety. The following fish breeding indices were determined for the experimental/control fodders after 47 days of testing: feeding ratio 0.670/0.467; mean daily gain 1.255/1.547 %; mean final weight 0.630/0.735 g; absolute weight growth 0.287/0.392 g; mortality (survival) 0.50 (99.50)/0.48 (99.52) %. Increasing of the water and minerals content and noticeable decreasing of the protein and fat content were detected in tissues of the control samples of fry by comparative biochemical analysis before and after the testing, whereas the content of protein and minerals had increased in tissues of the experimental samples. Thus, suitability and effectiveness of the experimental starter fodder for rearing of juvenile chum salmon in the low-temperature environment is proven by combination of several indices. To intensify the weight gain of juveniles, the experiments will be continued to adjust the composition of mixed feed for juvenile chum salmon in the cold-water conditions, with a principal restriction of the growth intensifiers (hormones) use. The starter compound feed developed in TINRO is recommended for using in rearing of chum salmon fry.